The prevalence of post-traumatic stress disorder among emergency medical services personnel in Saudi Red Crescent Authority, Riyadh, Saudi Arabia - Alanazi, Sattam Zaid; Abusharha, Ali; Afsar, Tayyaba; Trembley, Janeen H.; Razak, Suhail (Frontiers in Psychiatry, 2024)
Background Determining the prevalence of PTSD and contributing variables among (EMS) specialists was the goal of the current investigation. Furthermore, limited evidence exists regarding the application of PCL-5 for EMT practitioners, and the incidence of PTSD among different age groups and genders in Saudi Arabia. Methods This cross-sectional descriptive study includes 211 prehospital care providers of the Saudi Red Crescent Authority stations in Riyadh. The randomization was done using Google Forms into subgroups according to participants’ gender, years of experience, occupations, and average working hours. The presence and severity of PTSD symptoms were evaluated using the 20-item PTSD Checklist for DSM-5 (PCL-5) self-report questionnaire. Data were analyzed using Pearson Chi-Square, Mann-Whitney and Kruskal-Wallis tests. The reliability statistics were calculated using Cronbach’s Alpha for the 20-survey questionnaire. Results The comparison of PCL-5 total scores indicated more PTSD symptomatology among females (1.61 + 0.799) as compared to male workers (1.13 + 0.642). The total score of PTSD demonstrated no statistically significant (P=0.79) differences between our age group classifications. In terms of the participants’ city (Riyadh), the total PTSD score was less than the cutoff point which is 31. PTSD total score may not be affected by working experience as indicated by the non-significant difference in prevalence among EMT practitioners having <5 years, 5-10 years and above 10 years of working experience (P=0.215 with X2 = 3.076). PTSD incidence is affected by the type of occupation as statistically significant differences between groups (P=0.001) were recorded depending on the position and responsibilities of EMS practitioners. PTSD is also affected by average working hours per week, and there were statistically significant differences between groups (P=0.001). Conclusion The total score of PTSD in the case of emergency service practitioners was found to be 33.7% among all the research participants, which may be regarded as a high prevalence when compared to the general population. Our investigations would contribute to a better understanding of the underlying factors of mental stress in EMS specialists in Saudi Arabia and to the development of adequate mental health practices.